ANALYSIS OF CRIMINAL REPORTING DISCOURSE ON MEDIA ONLINE - Adi Saputra; Anis Endang SM; Bayu Risdiyanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
The news delivered is various, including news about crime. Crime is always interesting to broadcast and of course a lot of public interest and is constructed to produce interesting news and broadcast in the media, including online media. This study aims to explain and find out the discourse from the news of the case of one family in CurupTimur conducted by the online newspapers BETVNews.com, Harian Rakyat Bengkulu.comand BengkuluToday.com. This research uses descriptive qualitative method andTeunA Van Dijk's discourse analysis theory by conducting interviews, observations and documentation. The results of this study indicate that between the three media each gives an overview of the discourse of the case BETVNews.com focuses more on the chronological facts of events in more detail. Whereas Harian Rakyat Bengkulufrom the point of news is more balanced between the perpetrators and victims, it is more about how to get balanced news, and for a more flexible title, it is not limited by space and the format must be interesting to read. And finally, BengkuluToday.com reporting is made by prioritizing dramatic news writing, because this case is a criminal incident..